2017
DOI: 10.1002/hyp.11192
|View full text |Cite
|
Sign up to set email alerts
|

Trends in precipitation extremes over the Yellow River basin in North China: Changing properties and causes

Abstract: The Mann-Kendall test, composite analysis, and 68 high-quality meteorological stations were used to explore the spatiotemporal variations and causes of precipitation extremes over the Yellow River basin (YRB) during the period of 1960-2011. Results showed that (a) the YRB is characterized by decreases of most precipitation indices, excluding the simple daily intensity index, which has increasing trends in most locations, suggesting that the intensity of rainfall and the probability of occurrence of droughts ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 58 publications
2
38
0
1
Order By: Relevance
“…when height is increased R20 stops decreasing, which is also coherent with the positive pattern of rainfall through elevation (Yao et al ., ). Also, a significant negative correlation for R20 has been reported by Gao and Wang (). In the range 1,585–2,425 m, RX5day, SDII, R10, R20, CDD and PRCPTOT had a negative correlation between moderate and weak (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…when height is increased R20 stops decreasing, which is also coherent with the positive pattern of rainfall through elevation (Yao et al ., ). Also, a significant negative correlation for R20 has been reported by Gao and Wang (). In the range 1,585–2,425 m, RX5day, SDII, R10, R20, CDD and PRCPTOT had a negative correlation between moderate and weak (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…This reduction in CDD is coherent with the precipitation increase that occurs when elevation increases (Yao et al ., ). Other studies have also found a significant correlation between CDD and elevation (Zhang et al ., ; Gao and Wang, ). In the same way, for the range 1,995–2,425 m, the majority of correlations were negative and varied from moderate to weak; the unique index with a positive correlation was CDD, which was weak (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…This basin has undergone climate variability and land use change in recent decades [32]. Studies showed that in the central-south Yellow River basin the intensity of precipitation extremes increased between the years 1986 and 2011, and may have resulted in increased surface runoff [33,34]. The annual average air temperature showed a significant increasing trend in recent decades which may induce the occurrence of increased evapotranspiration [13,35].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas drought is a natural event, which results from receiving less precipitation than the long‐term average for an extended period of time (Smakhtin, ), flood is a rather short‐duration phenomenon that originates from an extremely high amount of precipitation. Because the occurrence of these natural hazards is closely interconnected with the amount and frequency of extreme precipitation, analysis of trends and variations in extreme precipitation has recently received a great deal of attention (Du, Xia, Zeng, She, & Liu, ; Gao & Wang, ; Hosseinzadehtalaei, Tabari, & Willems, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the occurrence of these natural hazards is closely interconnected with the amount and frequency of extreme precipitation, analysis of trends and variations in extreme precipitation has recently received a great deal of attention (Du, Xia, Zeng, She, & Liu, 2014;Gao & Wang, 2017;Hosseinzadehtalaei, Tabari, & Willems, 2017).…”
Section: Introductionmentioning
confidence: 99%